2020
DOI: 10.1093/ssjj/jyaa023
|View full text |Cite
|
Sign up to set email alerts
|

Property Systems and Economic Growth in Japan, 730–1874

Abstract: New estimates on the premodern economic growth of Japan, based on more concrete evidence, have been presented. We revise the estimates of Japan’s gross domestic product (GDP) from the mid-eighth century to the mid-19th century and its population in the 12th century and describe the institutional transformations that correspond to the output changes. The revision of output and population results in updated estimates of per capita GDP for the medieval period and extension of the growth estimates in the early mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Population increased rapidly after 1600 due to a civil war lasting over one and a half centuries coming to an end (see the right axis of Figure 4). Due to the lack of population surveys for 1600, estimates for the population at this time vary between 12 to 22 million, but I use the 17 million figure following Bassino et al (2019) and Nakabayashi et al (2020). The next observations are from 1721, where the best estimates derived from the population census suggest a vast increase to 31 million (Kitō 1996;Farris 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Population increased rapidly after 1600 due to a civil war lasting over one and a half centuries coming to an end (see the right axis of Figure 4). Due to the lack of population surveys for 1600, estimates for the population at this time vary between 12 to 22 million, but I use the 17 million figure following Bassino et al (2019) and Nakabayashi et al (2020). The next observations are from 1721, where the best estimates derived from the population census suggest a vast increase to 31 million (Kitō 1996;Farris 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The second alternative narrative is by Bassino et al (2019) and recently updated by Nakabayashi et al (2020), which is based on GDP per capita estimates shown in Figure 12. They place the beginnings of divergence in the medieval period.…”
Section: Reconciling the Many Divergencesmentioning
confidence: 99%
“…The state provides formal institutional foundations for each market to function; examples include the security of property rights, provision of legal basis for credit cooperatives, establishment of formal agricultural banks and implementation of provincial rice inspections. The state's role is supported by its capacity to levy taxes and provide public goods (Nakabayashi et al, 2020; Sakane, 2011, pp. 234–8; Sng & Moriguchi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The diversification of crops progressed slowly. The share of rice decreased, while the share of other commodities such as sericulture, 3 For up-to-date long-term estimates of Japan's GDP (730-1874), see Bassino et al (2019) and Nakabayashi et al (2020). 4 GDP estimates for countries other than Japan are from the Maddison Project Database, version 2013 (Bolt & van Zanden, 2014).…”
Section: Agricultural Production and Consumptionmentioning
confidence: 99%
See 1 more Smart Citation